PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII 2 SMPN 34 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Wahyuni, Devi; Ibrahim, Bedriati; Ahmal, Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This research was motivated by the social studies (Social Sciences)learning outcomes of grade VII 2 SMPN 34 Pekanbaru students, which were still wellbelow the KKM established by the school, namely 75. This study aims (1) determine theactivities of teachers by applying the cooperative learning model. Match at SMPN 34Pekanbaru, (2) To determine the activities of students using the Make A Match type ofcooperative learning model at SMPN 34 Pekanbaru, (3) To determine student learningoutcomes in social studies with the application of the Make A Match type cooperativemodel in class VII 2 SMPN 34 Pekanbaru. This research is a Classroom ActionResearch (CAR) that consists of 2 cycles. Each cycle consists of 4 phases, namelyplanning, executing actions, observing and reflecting. The subjects were students ofclass VII 2 SMPN 34 Pekanbaru for the 2019/2020 academic year, 40 students in total.The research tools used were teaching aids and data collection tools. The learningmaterials consist of a lesson plan and question and answer cards. The data collectiontools used were the observation sheet and the learning outcomes test sheet. Based onthe data analysis of the observation of teacher and student activity, it can be concludedthat there is an improvement in the learning process after applying the Make A Matchcooperative model in learning activities. In the initial conditions, the learning outcomesreached a percentage of 45%, then increased to 65% in the first cycle and to 85% in thesecond cycle. Based on the results of the study, it can be concluded that the applicationof the Make A Match type cooperative model can improve the learning process andimprove the learning outcomes of class VII 2 SMPN 34 Pekanbaru students.Key Words: Cooperative Learning Model Make A Match Type, Social Studies LearningOutcomes, Classroom Action Research (CAR)